Comparative Study of Hypolipidemic Effects of Momordica Charantia (Karela) with Atorvastatin in Fat Fed Rats - Sharmin, Zinat Rehana; Akter, Muqbula Tasrin; Rahman, Rifayet; Hoque, Mahbubul; Khan, Ismail; Mosaddek, Abu Syed Md. (Journal of Human Health Research, 2017)
Background: Disorders of lipid metabolism are manifested by elevation of the plasma concentration of the various lipid and lipoprotein fractions and the result, predominantly cardiovascular diseases. Lipid research clinic’s coronary primary prevention trial has provided useful information on the reduction of plasma cholesterol level in hyperlipidemic subjects by diet and drug therapy and thus the reduction in risk of myocardial infarction and death. Conventional lipid lowering drugs are used for lowering lipid level. But in the last few years’ herbal drugs are gaining popularity in the management of hyperlipidemia. In this study we compare the hypolipidemic effect of MomordicaCharantia (MC) with atorvastatin, a commonly used hypolipidemic drug. Methods: The present experimental study was done in the pharmacology department of Dhaka Medical College during the period of July, 2011 to June, 2012. For this study a total number of 30 Norwegian rats of either sex were selected. They were divided into 5 groups each comprises of 6 rats. In the experiment group A was given normal diet with high fatty diet (1.5 ml olive oil plus 1% cholesterol) which was control group and other experimental groups (B,C,D,) were allowed to feed a high fatty diet along with fresh juice of MomordicaCharantia (in different doses) for 10 days. Another experimental group, E was given high fatty diet along with atorvastatin (0.14mg/kg/day) for 10 days. Rats were sacrificed on 11th day and blood was collected by cardiac puncture for estimation of serum lipid profile. Results: After administration of fatty diet in group A for 10 days, there was significant increased total cholesterol (TCL), low density lipoprotein (LDL) and triglyceride (TG) levels. Concomitant administration of fatty diet and fresh juice of MC (in different doses) daily for 10 days in group B,C,D reduced serum TCL, LDL and TG levels which was more significant in higher doses in comparison to atorvastatin given group E. Conclusion: The present study provides a rationale for use a new herbal medicine much needed for the reduction of serum lipid levels.MomordicaCharantia could be useful in hyperlipidemic conditions. They are as effective as a standard lipid lowering agent- atorvastatin.
Keywords: Momordica Charantia; Total cholesterol; Low density lipoprotein; High density lipoprotein; Triglyceride.